Observation of Voriconazole in the Treatment of Liver Failure Complicated With Invasive Pulmonary Fungal Infection Induced by Chinese Patent Medicine in Teenagers: 2 Case Reports - Su, Qian; Pan, Jinjin; Zhang, Li; Xia, Lingling; Gao, Yufeng; Li, Jiabin (Frontiers in Pharmacology, 2022)
Background: Drug-induced liver injury (DILI) caused by Chinese patent medicine is increasing in China. The incidence of invasive fungal infections (IFI) is increasing due to suppression of immune function in greater numbers of patients. Invasive procedures such as deep vein catheterization and the use of glucocorticoids are also predisposing factors to IFI. The clinical presentation of IFI in teenagers is often atypical, challenging to diagnose, difficult to treat and is associated with a high fatality rate. Case presentation: Herein we report 2 teenagers with liver failure after receiving oral Chinese patent medicines. Case 1 was a 14-year-old boy who presented with subacute liver failure who had been administered a Chinese patent medicine that included acetaminophen. Administration of glucocorticoids and non-bioartificial liver treatment improved his condition. Subsequently, invasive pulmonary Aspergillus (IPA) was diagnosed and was successfully treated with voriconazole for 85 days. Case 2 was a 17-year-old girl with acute liver failure after taking the Chinese patent medicine QubaiBabuqi tablets for vitiligo. Chest computed tomography (CT) revealed multiple pulmonary nodules with an intermittent low-grade fever, she was diagnosed with IPA. She was initially treated with caspofungin (23 days) and then voriconazole (406 days) for 429 days. Liver function returned to normal and lung lesions were absorbed in 2 patients. At the same time, two to three histopathological examinations of the liver biopsy showed that the drug-induced autoimmune-like phenomena could be improved by glucocorticoid therapy. Conclusion To our best knowledge, this is the first report to the successful treatment of 2 cases of liver failure (Child-Pugh class C) caused by Chinese patent medicine complicated with IPA in teenagers. Drug-induced autoimmune-like phenomena could be improved by glucocorticoid therapy.